Empowering Women in Tech Innovation and Entrepreneurship: A Qualitative Approach - Teresa Felgueira; Teresa Paiva; Catarina Alves; Natália Gomes (Education Sciences)
Women’s participation and leadership in technology and entrepreneurship are crucial for advancing innovation and ensuring inclusive economic development. Despite progress in gender equality, women in tech face challenges like under-representation and systemic biases. This research delves into the multifaceted experiences of women in tech innovation and entrepreneurship, highlighting the barriers they face and the strategies they use to overcome them. This study used a qualitative, observational design with semi-structured interviews and thematic analysis to explore the experiences and perceptions of entrepreneurial women in the Science, Technology, Engineering, and Mathematics (STEM) field. It was possible to conclude that entrepreneurial women exhibit a strong sense of autonomy, competence, and leadership, enabling them to manage their ventures independently and effectively. Also, the success of entrepreneurial women is multifaceted, combining personal fulfilment, professional achievements, and financial stability, with positive feedback and recognition playing a key role. Building strong social and supportive relationships is vital for entrepreneurial women, providing a sense of belonging, community, and emotional support. In this context, to empower women in STEM and entrepreneurship, Higher Education Institutions (HEIs) should promote entrepreneurship as a career path, provide practical and value-based education, and foster a work environment of trust, communication, and continuous learning.